Implementing STEM in Improving Critical Mathematical Thinking Skills and Self-Efficacy - Desti Sapitri; Lukman El Hakim; Tian Abdul Aziz (Penerbit Presisi Pustaka, 2026)
Advances in science and technology are opening doors to a variety of jobs in new fields. Skills in software, programming, data analysis, and digital literacy are essential, reflecting the changes and evolution in the demands of the workplace and everyday life along with technological advancements. The independent curriculum reflects the adjustments in the education system to meet the demands of the times and the needs of society. The independent curriculum emphasizes active learning and the development of 21st-century skills. According to Zubaidah (2018), critical thinking skills are fundamental skills in 21st-century learning.